The Compensation for Punitive Damages (Revista da Faculdade de Direito, Universidade de São Paulo, 1995)
The moral damage is a harm to the values of the human being. It affects one's personality and social prestige. Therefore, the reparation of such illicit derives from the principles of the jus naturae (Natural Law). This current essay intends to demonstrate that our legal system should care not only about the protection of the economic values, but also the defense of the moral wealth. The moral damage must be fully remedied by prevision of private seclusion and compensatory satisfaction, both applied with equity.